MTOR Pathway Activation Assessed by Immunohistochemistry in Cervical Biopsies of HPV-associated Endocervical Adenocarcinomas (HPVA): Correlation With Silva Invasion Patterns. Issue 7 (9th August 2021) - Segura, Sheila; Stolnicu, Simona; Boros, Monica; Park, Kay; Ramirez, Pedro; Salvo, Gloria; Frosina, Denise; Jungbluth, Achim; Soslow, Robert A.
Abstract : Supplemental Digital Content is available in the text. Abstract : The Silva pattern of invasion, recently introduced to stratify patients at risk for lymph node metastases in human papillomavirus-associated endocervical adenocarcinomas (HPVAs), can only be assessed in cone and loop electrosurgical excision procedure excisions with negative margins or in a hysterectomy specimen. Previous studies found associations between destructive stromal invasion patterns (Silva patterns B and C) and mutations in genes involved in the MEK/PI3K pathways that activate the mammalian target of rapamycin (mTOR) pathway. The primary aim of this study was to use cervical biopsies to determine whether markers of mTOR pathway activation associate with aggressive invasion patterns in matched excision specimens. The status of the markers in small biopsy specimens should allow us to predict the final and biologically relevant pattern of invasion in a resection specimen. Being able to predict the final pattern of invasion is important, since prediction as Silva A, for example, might encourage conservative clinical management. If the pattern in the resection specimen is B with lymphovascular invasion or C, further surgery can be performed 34 HPVA biopsies were evaluated for expression of pS6, pERK, and HIF1α. Immunohistochemical stains were scored semiquantitatively, ranging from 0 to 4+ with scores 2 to 4+ considered positive, and Silva pattern was determined in follow-up excisional specimens. Silva patterns recognized in excisional specimens were distributed as follows: pattern A (n=8), pattern B (n=4), and pattern C (n=22). Statistically significant associations were found comparing pS6 and pERK immunohistochemistry with Silva pattern (P=0.034 and 0.05, respectively). Of the 3 markers tested, pERK was the most powerful for distinguishing between pattern A and patterns B and C (P=0.026; odds ratio: 6.75, 95% confidence interval: 1.111-41.001). Although the negative predictive values were disappointing, the positive predictive values were encouraging: 90% for pERK, 88% for pS6 and 100% for HIF1α. mTOR pathway activation assessed by immunohistochemistry in cervical biopsies of HPVA correlate with Silva invasion patterns.